2020
DOI: 10.1002/humu.24052
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism, deafness, and renal dysplasia syndrome: 20 Years after the identification of the firstGATA3mutations

Abstract: The hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome is an autosomal dominant disorder caused by heterozygous mutations of the GATA3 gene. In the last 20 years, since the identification of the genetic cause of the HDR syndrome, GATA3 mutations have been reported in 124 families (177 patients). The clinical aspects and molecular genetics of the HDR syndrome are reviewed here together with the reported mutations and phenotypes. Reported mutations consist of 40% frameshift deletions or insertions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 65 publications
(87 reference statements)
0
30
1
Order By: Relevance
“…To date, several types of GATA3 mutations related to HDR syndrome have been reported in nearly 124 families (177 patients) worldwide. These include about 40% frameshift deletions or insertions, 23% missense mutations, 14% nonsense mutations, 6% splice site mutations, 1% in-frame deletions or insertions, 15% complete gene deletions, and 1% complete gene duplications [ 21 ]. Vidavalur et al [ 22 ] reported a male premature infant who was small for gestational age, with micrognathia and facial malformation, combined with hypoparathyroidism and bilateral sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several types of GATA3 mutations related to HDR syndrome have been reported in nearly 124 families (177 patients) worldwide. These include about 40% frameshift deletions or insertions, 23% missense mutations, 14% nonsense mutations, 6% splice site mutations, 1% in-frame deletions or insertions, 15% complete gene deletions, and 1% complete gene duplications [ 21 ]. Vidavalur et al [ 22 ] reported a male premature infant who was small for gestational age, with micrognathia and facial malformation, combined with hypoparathyroidism and bilateral sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a missense mutation in GATA3 was present in a family with relatives' ages 15 to 60 years with apparently non‐syndromic hearing loss. Ages at onset of the syndromic features of GATA3 are variable, with mean age of onset during childhood or early teenage years, but possible onset of the full spectrum of phenotypes as late as age 50 57 . It is still possible, therefore, that the affected relatives of this family will develop syndromic features.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that Gata3 loss-of-function in mice results in early lethality around E11 with severe defects including craniofacial anomalies (21,22). In addition, GATA3 mutations in human result in hypoparathyroidism, sensorineural deafness and renal disease (HDR) syndrome, a constellation of anomalies that also includes craniofacial defects such as CA (8,23). The fact that Gata3 is strongly expressed around the developing frontonasal process in combination with its connection to human disease motivated us to investigate the role of Gata3 in CA and its association with retinoid signaling (24).…”
Section: Investigation Of Critical Factors Associated With Retinoid Signaling During Primitive Choanae Formationmentioning
confidence: 99%